Effects of Water Quality on the Seasonal Variability of Gonadosomat-ic Index (GSI), Hepatosomatic Index (HSI), Stomach Repletion Index (SRI) and Condition Factor (K) of Clarias gariepinus and Oreo-chromis niloticus from River Ngadda, Borno State – Nigeria: Effect of Water Quality on Fish Health - Mathias Bwala; Ezra Gaya; Ahmed Nayaya; Toma Buba (Department of Aquaculture, 2026)
Environmental stressors such as water quality depletion, micro-(nano) plastics (MNPs), heavy metals, and endocrine-disrupting chemicals (EDC) may exert behavioral, developmental, physiological, and reproductive stress on organisms, particularly fish in the aquatic ecosystems. Ecotoxicological biomarkers such as the gonadosomatic index (GSI), hepatosomatic index (HSI), stomach repletion index (SRI), and condition factor (K) provide insights into the fish’s health, nutritional status, and reproductive dynamics. This study assessed the influence of water quality on GSI, HSI, SRI, and K in Clarias gariepinus and Oreochromis niloticus from River Ngadda, Maiduguri, Borno State, Nigeria, across dry and wet seasons. Results showed that all measured parameters were within the permissible limits of the National Environmental Standards & Regulations Enforcement Agency (NESREA) and the World Health Organization (WHO). During the dry season, pH ranged from 7.27 ± 0.24 to 7.71 ± 0.19, while TDS ranged from 179 ± 22.4 to 463 ± 287.5 ppm. Nitrate concentrations during the wet season ranged from 26.35 ± 7.04 to 29.80 ± 8.03 mg/L. Seasonal variations were observed in fish biomarkers, with male C. gariepinus exhibiting GSI values of 0.531 ± 0.5–4.428 ± 1.4 (wet season) and 0.919 ± 0.9–2.665 ± 0.3 (dry season). In O. niloticus, GSI of the females peaked during the dry season (10.542 ± 3.1–14.737 ± 4.4), while others also showed pronounced seasonal and species-specific patterns. Canonical correlation analysis revealed strong relationships (r > 0.90) between water quality variables and fish physiological and reproductive indexes, suggesting a strong relationship between water quality and the fish’s health.